Romney and the Northamerican primaries. A new position for the centre right - Marco, José María (Razón y fe, 2018)
Some of the singularities of the electoral system of the United States are presented in this essay: the importance and the meaning of the so-called primary elections. In our case, we analyze the triumph of the republican candidate Mitt Romney and we outline his possible program, from the new position of a renewed centre right, in contrast to the one that the actual president Barack Obama will defend on the November elections.
Keywords: United States; primaries; Romney; centre right; human rights